Hardy-Weinberg Equilibrium in different mitochondrial haplogroups of four genes associated with neuroprotection and neurodegeneration - Sheida MEHRPOUR; Camila Ronqui RODRIGUES; Renata Carmona FERREIRA; Marcelo Ribeiro da Silva BRIONES; Acary Souza Bulle OLIVEIRA (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Malfunctioning or damaged mitochondria result in altered energy metabolism, redox equilibrium, and cellular dynamics and is a central point in the pathogenesis of neurological disorders such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease and Amyotrophic Lateral Sclerosis. Therefore, it is of utmost importance to identify mitochondrial genetic susceptibility markers for neurodegenerative diseases. Potential markers include the respiratory chain enzymes Riboflavin kinase (RFK), Flavin adenine dinucleotide synthetase (FAD), Succinate dehydrogenase B subunit (SDHB), and Cytochrome C1 (CYC1). These enzymes are associated with neuroprotection and neurodegeneration. Objective: To test if variants in genes RFK, FAD, SDHB and CYC1 deviate from Hardy-Weinberg Equilibrium (HWE) in different human mitochondrial haplogroups. Methods: Sequence variants in genes RFK, FAD, SDHB and CYC1 of 2,504 non-affected individuals of the 1,000 genomes project were used for mitochondrial haplogroup assessment and HWE calculations in different mitochondrial haplogroups. Results: We show that RFK variants deviate from HWE in haplogroups G, H, L, V and W, variants of FAD in haplogroups B, J, L, U, and C, variants of SDHB in relation to the C, W, and A and CYC1 variants in B, L, U, D, and T. HWE deviation indicates action of selective pressures and genetic drift. Conclusions: HWE deviation of particular variants in relation to global populational HWE, could be, at least in part, associated with the differential susceptibility of specific populations and ethnicities to neurodegenerative diseases. Our data might contribute to the epidemiology and diagnostic/prognostic methods for neurodegenerative diseases.